Peningkatan Kemampuan Membaca Al-Qur’an Peserta Didik Melalui Metode Albarqy Pada Mata Pelajaran Al-Qur’an Hadits Fase E - Maria, Anly; Nabila, Nisa (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
This study discusses improving students' ability to read the Qur'an through the albarqy method in the Qur'an Hadith subject. This is based on the ability to read the Qur'an, which is an individual's skill to read the Qur'an properly and correctly in accordance with the applicable rules. However, in reality, the ability of phase E students, especially those in class X-B MAN 1 Garut, to read the Qur'an is still relatively low. This is evidenced by the results of pre-research observations which show that only about 27.8% of the total 36 students have the ability to read the Qur'an. Therefore, a solution is needed to improve this, one of which is by applying the Albarqy method. The purpose of this study is to describe the ability of students to read the Qur'an through the application of the Albarqy method to improve the ability of students to read the Qur'an in the Qur'an Hadith phase E subject at MAN 1 Garut. The method used was Classroom Action Research (CAR). Data collection techniques included observation, interviews, and tests. Based on the results of the classroom action research conducted in two cycles, there was an increase in students' ability to read the Qur'an in cycle I to 44.4%, then another increase in cycle II to 86.1%. It can be understood that there was an increase in students' ability to read the Qur'an with a significance of 16.6% from the pre-cycle to cycle I and 41.7% from cycle I to cycle II. Thus, overall, there was an increase in students' ability to read the Qur'an with a significance of 58.3% from the pre-cycle to cycle II.  Keywords: Student Ability; Reading the Qur'an; Albarqy Method